Hamka and the School of Modernists in Minangkabau - Ahmad Nabil Amir; Tasnim Abdul Rahman (Sunan Kalijaga: International Journal of Islamic Civilization, 2025)
The study aims to provide a concise historical background of Islamic reform movement in West Sumatera with particular reference to the idea of Haji Abdul Malik Karim Amrullahor better known for his pseudonym Hamka (1908-1981). The main issues explored is the  socio-religious reform advocated by Hamka in the quest of modernity, including his enriching narrative of renewal and spiritually enlightening  vision. To this end, this research aims to highlight his key works and reformist aspiration , examines  the influence they generated to further his cause, and asseses his enduring legacy and monumental contribution to the history and tradition of reform in the Malay world. This study uses normative and qualitative approach through content analysis. The data was conceptually analysed using descriptive, comparative and integrative method. The study found that Hamka’s modern idealism was instrumental in driving new consciousness of Islamic movement for reform (islah) and renewal (tajdid) in the Malay world contributing to unprecedented religious struggle that erupted in the late 20th century in Malay Archipelago. It reflected the force of modern ideas espoused by the leading Egyptian-mufti and polymath Shaykh Muhammad Abduh (1849-1905) that had brought decisive and greatest influence in the region. This study shows how Hamka’s work present higher Islamic ideals and principles. It also highlights the dynamic aspirations of Kaum Muda (the young faction) in their socio-religious development.